Adapting Sustainable Development Goal 1 (SDG 1) "No Poverty" to Eliminate the Phenomenon of Child Beggars in Malaysia - Ab Rahman, Nurul Hidayat; Abdullah, Nur Natasha Eiman (Kanun: Jurnal Undang-undang Malaysia, 2022)
"No Poverty" (SDG 1) is the first of the 17 Sustainable Development Goals 2030 that serves as the foundation for the fulfilment of other fundamental human rights such the right to life, health, education, participation, and others for children. Child beggars, in particular, are one of the most vulnerable groups in terms of human rights protection because economic insecurity causes this group to endure social, economic, and environmental discrimination. This article was written to examine the extent of legal protection provided to child beggars in Malaysia under the Convention on the Rights of the Child (CRC) and the Child Act 2001 (Act 611) in order to identify shortcomings that may be addressed through the adaptation of SDG 1. This writing is a purely legal study that employs qualitative methodology and content analysis. Shortcomings in protection that have been identified are outdated and obsolete regulations, the absence of complete data on child beggars, and inefficient poverty reduction measures. As a result, this article suggests the prohibition of child begging through the adoption of new legislation, the drafting of new policies to eradicate poverty, as well as the enhancement of child welfare services. Keywords : Human rights, poverty, sustainability, Sustainable Development Goals 2030, child beggars, SDG 1 Full text : PDF